Talking circle: FSKM Colloquium (01/2022) / Nadiah Mohamed, Nurul Aityqah Yaacob and Nor Ashikin Sahrom - Mohamed, Nadiah; Yaacob, Nurul Aityqah; Sahrom, Nor Ashikin (Universiti Teknologi MARA, Negeri Sembilan, 2022)
On May 31st, 2022, the Department of Computer Science & Mathematics (FSKM) of UiTM Negeri Sembilan Kampus Kuala Pilah hosted the Talking Circle: FSKM Colloquium (01/2022). In this session, the Canva application was presented by Siti Noor Dina Ahmad to the participants who were among the FSKM lecturers. Canva was chosen above other free graphic design software due to its flexibility to change the transparency of each piece. This application manages to generate a range of amazing visuals, such as fascinating overlays and textured effects, for backdrops, photos, icons, and logos. It is advantageous for instructors to have various options for creating compelling and interactive course materials. Overall, all participants were happy with the Canva application and eager to participate in another future session.